Growth and yield of cauliflower with brackish waters under hydroponic conditions - Mairton G. da Silva; Leandro F. da Costa; Tales M. Soares; Hans R. Gheyi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Historically, and in the aggravating climate change scenario, droughts are increasingly severe in arid and semi-arid regions, limiting the use of irrigation. As an alternative for these regions, brackish waters have been used, despite the severe risks of soil salinization, as well as losses in crop production and quality. Thus, the adoption of adequate technologies should mitigate or control the impacts caused by salt stress. Therefore, in the present study two experiments were conducted to evaluate the cultivation of cauliflower with brackish waters using a nutrient film technique (NFT) hydroponic system from July to October 2019 (winter-spring) and from October 2019 to January 2020 (spring-summer). Cauliflower plants were subjected to six values of ECw: 0.3 - control (without NaCl), 1.5, 2.5, 3.5, 4.5, and 5.5 dS m-1 (with NaCl), in a randomized block design with six replicates. For the leaf blade area at inflorescence harvest, reductions per dS m-1 increment in ECw of 7.22 and 6.41% were found in the winter-spring and spring-summer experiments, respectively. The quality losses of cauliflower inflorescences were more pronounced in the spring-summer experiment, varying according to the ECw used. Therefore, it is possible to grow cauliflower hydroponically under ECw of up to 5.5 dS m-1; however, in the hottest seasons these waters should be reserved and used only for the preparation of nutrient solutions or replacement of water consumed by plants.